Acinetobacter infections: Overview and treatment dilemma - Sana Ali (Wolters Kluwer Medknow Publications, 2020)
Introduction: Acinetobacter species are known to cause serious hospital-acquired infections (HAIs), especially in the intensive care unit (ICU). The aim of this study is to estimate the burden of such infections and also to determine their sensitivity to currently available antimicrobials. Materials and Methods: The study was conducted at a tertiary care hospital in New Delhi from June 2017 to December 2018 to estimate the number of Acinetobacter isolates from clinical samples. Organisms were identified, and their susceptibility to antimicrobials was tested using VITEK-2 automated system. Results: Of the total 701 isolates recovered from clinical samples during the study, 28 (4%) were Acinetobacter species. Among them, majority (57%) of the isolates were isolated from ICU patients. Respiratory specimen yielded maximum number of isolates (46.4%). About 71.4% of isolated strains were extremely drug resistant, 10.7% were multidrug resistant, whereas 3.5% were pandrug resistant (PDR). PDR strains were found to be resistant to even the last resort antibiotics such as tigecycline and colistin. Acinetobacter baumannii was also the most common cause for HAIs (57.1%), resulting in overall mortality of 42.8% due to HAI. Conclusion: Acinetobacter has gained great importance in health-care setting by posing serious threat to patients, which is compounded by its tendency of antibiotic resistance. HAIs are usually difficult to treat, resulting in therapeutic failure and increased mortality. It signifies the need to implement strict preventive measures in hospitals and to use higher antimicrobials or combination therapy judiciously.